ASSESSING GRIT AND WELL-BEING OF MALAYSIAN ESL TEACHERS: APPLICATION OF THE PERMA MODEL (Malaysian Journal of Learning and Instruction, 2022)
Purpose – Seligman’s well-being theory of PERMA has been proven fruitful in defining various well-being constructs across different fields of study. With a growing interest in teacher psychology research abroad, PERMA has been unveiled as a rewarding prospect for the well-being of second language (L2) teachers. Nonetheless, the contribution of PERMA to the well-being and grit of L2 teachers in Malaysia remains unclear. Thus, this study (1) examined the influence of PERMA on the well-being and grit of Malaysian teachers of English as a second language (ESL); and (2) analyzed the mediating impact of positive emotion in the relationship between grit and well-being.Methodology – A priori power analysis was conducted to identify the sample size for this study. Hence, a convenience sample of 91 primary ESL teachers from Kuala Lumpur participated in this cross-sectional study. Data obtained were analyzed via multiple regression and mediation analysis using SPSS v20. The analysis of the indirect effects of the mediation model was complemented with a bootstrap procedure based on Hayes’s PROCESS Macro.Findings – The regression analysis confirmed the significant impact of PERMA on both well-being and grit. Analysis of the regression coefficients (β) displayed that engagement and accomplishment influenced significant changes in grit. Engagement was also a significant predictor of well-being. The mediation model portrayed positive emotion as a partial mediator in the association between grit and well-being.Significance – The meaningful interaction of PERMA with well-being and grit may not only encourage ESL teachers to flourish, correspondingly, it may elevate the well-being of learners in L2 classrooms.